On the nature of the omega tri-layer periodicity in rapidly cooled Ti-15Mo. (October 2015) - Bennett, J.M.; Barnard, J.S.; Stone, H.J.; Midgley, P.A.; Rugg, D.; Jones, N.G.
Graphical abstract: Abstract : High angle annular dark field (HAADF) images of the omega phase in metastable beta titanium alloys exhibit tri-layered periodicity. However, it is unclear if this indicates preferential site occupation, or is related to the structural modification of omega formation. Here, the periodicity was studied using a combination of HAADF imaging and electron energy loss spectroscopy. The results show that there is no preferential site occupancy or ordering and that the observed intensity variations are related to the imaging conditions.